3(b+4)=4(2b-3)

Simple and best practice solution for 3(b+4)=4(2b-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(b+4)=4(2b-3) equation:


Simplifying
3(b + 4) = 4(2b + -3)

Reorder the terms:
3(4 + b) = 4(2b + -3)
(4 * 3 + b * 3) = 4(2b + -3)
(12 + 3b) = 4(2b + -3)

Reorder the terms:
12 + 3b = 4(-3 + 2b)
12 + 3b = (-3 * 4 + 2b * 4)
12 + 3b = (-12 + 8b)

Solving
12 + 3b = -12 + 8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-8b' to each side of the equation.
12 + 3b + -8b = -12 + 8b + -8b

Combine like terms: 3b + -8b = -5b
12 + -5b = -12 + 8b + -8b

Combine like terms: 8b + -8b = 0
12 + -5b = -12 + 0
12 + -5b = -12

Add '-12' to each side of the equation.
12 + -12 + -5b = -12 + -12

Combine like terms: 12 + -12 = 0
0 + -5b = -12 + -12
-5b = -12 + -12

Combine like terms: -12 + -12 = -24
-5b = -24

Divide each side by '-5'.
b = 4.8

Simplifying
b = 4.8

See similar equations:

| -15-(15y-1)=2(7y-16)-y | | x^2+10z+24= | | 2+3(y-1)=3(2-y)+5 | | 9f-1=3f+9 | | 2(-8n-8)+3(4n+2)=5+n+3n-7 | | 5.75+.75=4.50+1x | | 6x-8x+5=-2(x+5)+7 | | -.8+4=-12 | | -42*2-7u*2+2u*2= | | -3.7=-37.0 | | 9-5t=64 | | 7-5z=17+5 | | 6x+-3=4x+9 | | 389.77=160+1.11x | | 3x+y=3y-3 | | -(-5x+10)-5x=-10 | | X+x-25+x-25(3)=275 | | 8-3(4-y)=-27 | | 70=16c-8 | | -45x+4=-12 | | 3-2m+7m=5m-3m | | 131-(6x+12)=6(x+9)+x | | 3[b+7]=30 | | 3d-12=9 | | N-25=-25 | | 4x+2=3(x-3)+6 | | -3x-10=-50 | | 2(5-1.7*1.4)=15.1-7*1.4 | | D+4.7=2.8t(12) | | N-35=-18 | | 12x+13=4x+7 | | 2(4x+1)=90 |

Equations solver categories